(untitled) - Axbey, Susan (Harlow, 1984)
Journeys is a course for pre-intermediate to intermadiate students of English. It follows Operation Drake, the real-life journey of exploration around the world undertaken by a group of young people from many different countries.
Keywords: English language,Tiếng Anh; Text-books for foreign speakers,Giáo trình dành cho người nước ngoài